Labor Market Power - David Berger; Kyle Herkenhoff; Simon Mongey (Institute of Labor Economics (IZA), 2019)
What are the welfare implications of labor market power? We provide an answer to this question in two steps: (1) we develop a tractable quantitative, general equilibrium, oligopsony model of the labor market, (2) we estimate key parameters using within-firm-state, across-market differences in wage and employment responses to state corporate tax changes in U.S. Census data. We validate the model against recent evidence on productivity-wage pass-through, and new measurements of the distribution of local market concentration. The model implies welfare losses from labor market power that range from 2.9 to 8.0 percent of lifetime consumption. However, despite large contemporaneous losses, labor market power has not contributed to the declining labor share. Finally, we show that minimum wages can deliver moderate, and limited, welfare gains by reallocating workers from smaller to larger, more productive firms.
Keywords: E2; J2; J42; 330; wage setting; market structure; labor markets